Hubungan Iklim Kerja Panas dengan Status Hidrasi Pekerja: Literatur Review - Fedora Ivena Thom; Annis Catur Adi (Media Gizi Kesmas, 2023)
Background: A hot working climate can result in excessive sweating so that it can cause dehydration in workers if it is not followed by adequate fluid intake. Workers with a hot work environment will interfere with the productivity of these workers. Objectives: The focus of this literature review is to determine the relationship between hot work environments and workers' hydration status. Methods: The journal articles reviewed were acquired from online databases such as science direct and google search without limitation of time and research results. The search for articles began on September 3 – September 15, 2022. Search for articles using the keywords "hot work climate, worker hydration status, heat exposure, hot work climate, hydration status”. Results: Based on the selection process, 11 articles were found that were suitable and used a cross sectional design. The eleven research articles show link relationship between a hot work climate and the hydration status of workers covering various types of professions and employment opportunities, both indoor work and outdoor work. Most showed a significant relationship.  Conclusions: Therefore, it can be concluded that hot temperatures or hot working climates can be a risk of dehydration in workers. Therefore, work agencies are expected to be warry of the workers's hydration level, especially those exposed to heat in an effort to increase work productivity.